2023
DOI: 10.1042/bst20221543
|View full text |Cite|
|
Sign up to set email alerts
|

Fast-forward on P-type ATPases: recent advances on structure and function

Abstract: P-type ATPase are present in nearly all organisms. They maintain electrochemical gradients for many solutes, in particular ions, they control membrane lipid asymmetry, and are crucial components of intricate signaling networks. All P-type ATPases share a common topology with a transmembrane and three cytoplasmic domains and their transport cycle follows a general scheme — the Post-Albers-cycle. Recently, P-type ATPase research has been advanced most significantly by the technological advancements in cryo-EM an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…NKA is classified as a member of the superfamily of P-type ATPases, which transport various compounds vectorially, ranging from H + to phospholipids, at the expense of ATP [ 60 ]. Due to its structural and functional characteristics, NKA is categorized as a type IIC-ATPase, sharing close relatives, such as H+/K + -ATPase and the sarcoplasmic/endoplasmic reticulum Ca2+-ATPase (SERCA) [ 61 , 62 , 63 , 64 ]. Molecular characterization has revealed that each NKA functional unit comprises two or three subunits: α, β, and γ or FXYD.…”
Section: Nka’s Role As An Electrogenic Pumpmentioning
confidence: 99%
“…NKA is classified as a member of the superfamily of P-type ATPases, which transport various compounds vectorially, ranging from H + to phospholipids, at the expense of ATP [ 60 ]. Due to its structural and functional characteristics, NKA is categorized as a type IIC-ATPase, sharing close relatives, such as H+/K + -ATPase and the sarcoplasmic/endoplasmic reticulum Ca2+-ATPase (SERCA) [ 61 , 62 , 63 , 64 ]. Molecular characterization has revealed that each NKA functional unit comprises two or three subunits: α, β, and γ or FXYD.…”
Section: Nka’s Role As An Electrogenic Pumpmentioning
confidence: 99%
“…K + homeostasis is central to enabling microbial survival under changing conditions. In many prokaryotes, high-affinity K + uptake at low extracellular K + concentrations is facilitated by the active K + pump KdpFABC 1 – 3 . Its chimeric composition of a K + channel and a P-type ATPase allows the complex to accumulate K + with an apparent affinity of 2 µM 4 .…”
Section: Introductionmentioning
confidence: 99%